KORELASI MINAT BELAJAR FISIKA SECARA DARING TERHADAP HASIL BELAJAR - Indriani, Wenni Tri; Sirait, Judyanto; Hamdani, Hamdani (Universitas Tanjungpura, 2024)
This study examines whether interest in learning physics online is related to student learning outcomes. The method used is a survey involving 102 respondents, each of which consists of 47 students of class X MIPA and 55 students of class XI MIPA at SMA Negeri 2 Mempawah. An online learning interest questionnaire was used to collect data, namely a questionnaire containing statements related to learning interest with a total of 23 statement items, and analyzed using the Spearman correlation formula. After analyzing, the correlation value of the two variables was 0.104 with a very weak interpretation of the correlation. In addition, the significance value of 0.299 shows that there is no correlation between interest in learning physics online and student learning outcomes and the percentage of influence of interest in learning physics online with learning outcomes of 1.08%. This shows that interest in learning physics online has very little effect on learning outcomes, resulting in a very weakcorrelation between the two. Therefore, teachers are expected to continue to innovate in online physics learning to increase students' interest in online physics learning.